Adaptive Agripreneurship: How CSR Partnerships Empower Disabled Farmers for Economic Independence - Nurhayati, Sri; Munggarani, Febi; Boriboon, Gumpanat; Jacob, Udeme Samuel; Lotfi, Fatima Zahra (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
This study examines the impact of Corporate Social Responsibility (CSR) partnerships on empowering disabled farmers within the